Spatial Fuzzy Clustering Algorithm for Optimizing Inclusive Da'wah Distribution Patterns - Karim, Abdul; Adeni, Adeni; Riyadi, Agus; Mursyid, Achmad Yafik (Universitas Muhammadiyah Mataram, 2025)
This article aims to identify and analyse the potential for inclusive da'wah in Central Java Province, Indonesia, by focusing on three fundamental aspects that determine the success of the da'wah process: the subject, the object, and the environment of the da'wah. This research applies an empirical approach through a series of spatial clustering analyses using the fuzzy geographically weighted clustering (FGWC) method to determine the optimum number of clusters in mapping the potential for da'wah. FGWC is a spatial analysis method that combines the concept of fuzzy clustering with a geographically weighted approach, allowing for more flexible and contextual identification of distribution patterns based on location. This method was chosen for its ability to handle uncertainty in spatial data as well as considering geographical variations in clustering. The data used in this study came from the Ministry of Religious Affairs of the Republic of Indonesia and the Central Statistics Agency (BPS) of Central Java Province, covering demographic, social, and religious data from 35 districts/cities in Central Java. The results of the FGWC analysis show that the optimum number of clusters is two, with districts/cities in the second cluster identified as having higher da’wah potential. This is evidenced by six high-value variables in the second cluster, while the first cluster has only one high-value variable. These findings have significant implications for inclusive da'wah strategies in Central Java. These results can be used as a strategy for mapping priority da'wah areas, allocating effective resources, and developing a more contextualised da'wah approach according to the characteristics of each cluster. This research's originality lies in applying the FGWC method in the context of da'wah mapping. This article is the first to combine spatial analysis with a study of the potential for inclusive da'wah, thus contributing to developing an interdisciplinary approach in the study of contemporary Islam in Indonesia.